2008
DOI: 10.1111/j.1752-0606.2008.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Focused Therapy for Families Coping with Suicide

Abstract: Solution-focused therapy is proposed as a model for families coping with suicide. The nature and incidence of suicide is described along with a consideration of the effects that suicide has on families and prevailing treatment approaches. Three case examples illustrate the application. Implications are discussed pertaining to the theory, practice, and research of solution-focused therapy for families coping with suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
0
14
0
3
Order By: Relevance
“…Prior to session one, couples completed an online assessment comprised of standardized self‐report measures assessing psychological well‐being, communication, feelings about one's partner, readiness for couple relationship change, and marital satisfaction. The intervention itself has five steps: (a) coconstructing goals (typically two to three), (b) identifying and amplifying exceptions (e.g., times when things have been better), (c) assigning tasks, (d) evaluating the effectiveness of the task, and (e) reevaluating the goals (de Castro & Guterman, ). During session one, couples and therapists reviewed assessments, coconstructed goals, discovered and amplified positive exceptions, and then coconstructed tasks that couples were asked to work on over 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to session one, couples completed an online assessment comprised of standardized self‐report measures assessing psychological well‐being, communication, feelings about one's partner, readiness for couple relationship change, and marital satisfaction. The intervention itself has five steps: (a) coconstructing goals (typically two to three), (b) identifying and amplifying exceptions (e.g., times when things have been better), (c) assigning tasks, (d) evaluating the effectiveness of the task, and (e) reevaluating the goals (de Castro & Guterman, ). During session one, couples and therapists reviewed assessments, coconstructed goals, discovered and amplified positive exceptions, and then coconstructed tasks that couples were asked to work on over 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Findings of the current research are consistent with the following studies: Stewart's research which showed that solution-focused couple therapy is effective on increasing relationship satisfaction, improving communicational skills and individual functions of couples; Eakes and colleagues research which indicated that solution-focused therapy changes the attitude of couples towards difficult conditions, creates a more positive view towards problems in couples, and strengthens their capabilities for coping with difficulties and problems [34,35]. In a research conducted by Christiansen on 24 couples, it was found that therapeutic experiences created by solution-focused approach have led to certain changes in their emotions, relationships and cognitions in their couple relationships [31]. Zimmerman, Prest .…”
Section: Discussionmentioning
confidence: 99%
“…How can you recognize your problem has been solved? These questions help the clients find different solutions for their problems and can be an important step in the process of change (24). The scale questions not only help them make progress but also help the couIran J Psychiatry Behav Sci.…”
Section: Discussionmentioning
confidence: 99%